2010
DOI: 10.2174/138620710791054286
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Discovery of Families of High Activity WGS Catalysts: Part I - History and Methodology

Abstract: State-of-art water gas shift catalysts (FeCr for high temperature shift and CuZn for low temperature shift) are not active enough to be used in fuel processors for the production of hydrogen from hydrocarbon fuels for fuel cells. The need for drastically lower catalyst volumes has triggered a search for novel WGS catalysts that are an order of magnitude more active than current systems. Novel catalytic materials for the high, medium and low temperature water gas shift reactions have been discovered by applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a recent study, Bebelis et al 64 have shown that the electrochemical supply of K + (an electropositive promoter) on a Pd catalyst deposited over β″-Al 2 O 3 , led to an increase in the RGWS reaction rate. In addition, Yaccato et al 11 reported that Ru is the best methanizer catalyst among a variety of metals, including Rh, whereas doping with alkaline metals (electropositive promoters) was found to decrease its methanation activity. Furthermore, they reported that Na-doping of Co increased its RWGS reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Bebelis et al 64 have shown that the electrochemical supply of K + (an electropositive promoter) on a Pd catalyst deposited over β″-Al 2 O 3 , led to an increase in the RGWS reaction rate. In addition, Yaccato et al 11 reported that Ru is the best methanizer catalyst among a variety of metals, including Rh, whereas doping with alkaline metals (electropositive promoters) was found to decrease its methanation activity. Furthermore, they reported that Na-doping of Co increased its RWGS reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical promotion of the CO 2 methanation catalysts by alkalis has also been investigated by several groups. 9,11,20,26,37,39 Yaccato et al 11 reported that when Ru is doped with alkaline metal electropositive promoters, a decrease in the methanation activity is observed. They also reported that Na doping of Co enhances the RWGS reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…For the conversion of gasoline into a hydrogen-rich gas for automotive PEMFCs the WGS reaction is commonly used to adjust the CO/H 2 ratio in syngas in order to remove CO from gas streams and to generate pure hydrogen. An overwiew of the present situation in this field has just been given by Yaccato et al 177 summarizing applied catalysts and focusing also on the Partnership for a New Generation of Vehicle (PNGV) cost target of 150$, which will be met with reactors of less than 6 L of volume and 3 kg in weight with cost/ weight/volume modeling of WGS reactors based on ceramic monoliths washcoated with Pt on Ceria catalysts. By scanning mass spectrometry version 2 (SMS-II) primary screening and data analysis by mass balance plots the same group found that using supported noble metals as catalysts WGS and methanation compete with each other and hence the selectivity of the WGS reaction strongly depends on the temperature of the reaction, the type of noble metal used, as well as the noble metal dispersion.…”
Section: Materials Development Examplesmentioning
confidence: 99%
“…In particular, the oxidation of carbon monoxide is of considerable relevance on account of its implications in many important industrial applications such as combustion exhaust gas, the development of CO detection devices, fuel gas cleanup, or the improved efficiency of CO 2 lasers 27,28. It is also closely related to the water‐gas shift reaction (WGSR; CO + H 2 O → CO 2 + H 2 ), which is utilized commercially for the synthesis of ammonia and petrochemicals 2936…”
Section: Introductionmentioning
confidence: 99%